1984
DOI: 10.1139/b84-001
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid vigour as indicated by early growth characteristics of Populus deltoides, P. nigra, and P. × euramericana

Abstract: The early growth of two hybrid Populus × euramericana (Dode) Guinier clones and a species clone each of P. deltoides Bartr. ex Marsh, and P. nigra L. in controlled environments was studied in terms of growth of organs, partitioning of dry weight among parts, and growth analysis parameters. The hybrid clones grew more vigorously compared with the species clones with regard to most of the parameters measured. From 7 weeks after planting onward, the hybrid clones had greater plant dry weight, leaf dry weight, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The effect of treatments and clones on relative growth rate was evaluated with analysis of variance using natural log-transformed total dry weight as the dependent variable (Cain andOrmrod 1984, Poorter andLewis 1986). Due to loss of trees and the resulting design imbalance, clone 216 was not included in Experiment 1 for this analysis.…”
Section: Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of treatments and clones on relative growth rate was evaluated with analysis of variance using natural log-transformed total dry weight as the dependent variable (Cain andOrmrod 1984, Poorter andLewis 1986). Due to loss of trees and the resulting design imbalance, clone 216 was not included in Experiment 1 for this analysis.…”
Section: Statisticsmentioning
confidence: 99%
“…The time by treatment effect was partitioned with orthogonal polynomials. A significant linear effect indicates constant relative growth rate during the experimental period while a significant higher order effect indicates variable relative growth rate (Cain andOrmrod 1984, Poorter andLewis 1986). Relative growth rate was calculated for each treatment by clone combination from the slope of log-transformed plant dry weight vs time using least-squares linear regression.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that leaves with high dry mass might have high photosynthetic accumulates that inhibit photosynthetic effi ciency. Cain and Ormrod (1984), studying two hybrids and two Populus clones, observed no signifi cant differences among clones in ratio of leaf mass to leaf area. In our study, there were no signifi cant differences among the clones for leaf area, leaf fresh or leaf dry mass.…”
Section: Discussionmentioning
confidence: 94%
“…A third method has been used -without further elaboration -by Cain and Ormrod (1984). In the present paper we describe this method in more detail and show that it incorporates the computational advantages of both the classical and the functional approach.…”
Section: Introductionmentioning
confidence: 99%